-48-3x=42+2x

Simple and best practice solution for -48-3x=42+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -48-3x=42+2x equation:


Simplifying
-48 + -3x = 42 + 2x

Solving
-48 + -3x = 42 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-48 + -3x + -2x = 42 + 2x + -2x

Combine like terms: -3x + -2x = -5x
-48 + -5x = 42 + 2x + -2x

Combine like terms: 2x + -2x = 0
-48 + -5x = 42 + 0
-48 + -5x = 42

Add '48' to each side of the equation.
-48 + 48 + -5x = 42 + 48

Combine like terms: -48 + 48 = 0
0 + -5x = 42 + 48
-5x = 42 + 48

Combine like terms: 42 + 48 = 90
-5x = 90

Divide each side by '-5'.
x = -18

Simplifying
x = -18

See similar equations:

| 6X9-/5X | | (14-2x)+40= | | 3(6+t)-1= | | 3(-5x-4)-2x=6 | | 3a^2+4a-7= | | 5x+2(6x-18)=117 | | 5m+-2-7m=20 | | 4=36/m | | 3a-5=5+a | | -6=14n | | 18x-4(3x+4)=(9x-5)-5(3x+7) | | 15xy-30y= | | 3d-2d-d+2d=8 | | F=1/2kw | | 3s-42=33 | | 6(c+2)=5(1-3c) | | 1x/5=14 | | 6[x+2]=60 | | 10d-7d=9 | | -x^3+3x+1.5=0 | | 4(1-7n)-5= | | d/7+75=81 | | -x^3+3x-1.5=0 | | 3(x-4)-2=5x | | 0.2(15y+2)=0.5(8y-3) | | 3x(x+17)=0 | | 1/2(3x=6)=3(x-2) | | 6x-5+2x=12 | | Y/6-7 | | 7sqrt(x-3)-2=8 | | m^2-h^2= | | Z-(11+3z)3=22-8z |

Equations solver categories